How to Consider Human Footprints to Assess Human Disturbance: Evidence from Urban Agglomeration in the Yellow River Basin - Sirui Luo; Xiangxue Li; Jie Yang; Xingwei Li (Land)
Natural processes are substantially impacted by human activity, and assessing human activity has significant ramifications for regional ecological conservation. The study developed an extended human footprint (HF) assessment model based on the theory of ecological effects and human pressures to evaluate human disturbances in the urban agglomerations of the Yellow River Basin using data from 2005 to 2020, revealing the spatiotemporal pattern in the region. The conclusions show that the HF value of urban agglomeration in the Yellow River Basin has steadily increased from 2005 to 2020, primarily driven by mining intensity and road construction. High HF areas are primarily concentrated in urban areas in the south-central of the region, with a tendency to spread outward. Medium HF areas are mainly distributed in the eastern part of the study area, and the spatial distribution increases year by year, extending outward from the center area. The moderately low and HF areas are mostly found in the mountainous areas of the northwest. Among the urban agglomerations in the Yellow River Basin, the Central Plains UA and Shandong Peninsula UA are the areas most heavily affected by human disturbance. The conclusions are instructive for the high-quality development of urban agglomerations in the Yellow River Basin.